USO DE FITOTERÁPICOS COMO ESTRATÉGIA PARA REDUÇÃO DO USO INDISCRIMINADO DE BENZODIAZEPÍNICOS NO TRATAMENTO DA ANSIEDADE (REMUNOM, 2024)
The study aims to investigate the use of herbal medicines as an alternative to reduce the prolonged consumption of benzodiazepines in the treatment of anxiety disorders, addressing the risks and complications of prolonged use of these medications. The research was carried out through a qualitative and descriptive literature review, consulting databases SCIELO, LILACS, PubMed and the Virtual Health Library (VHL), with articles published between 2015 and 2024. The results showed that the prolonged use of Benzodiazepines is often associated with negative effects on cognition, such as impairments in memory, attention and learning, in addition to elevated risks of dependence, especially in the elderly. On the other hand, the use of herbal medicines has therapeutic potential in controlling anxious symptoms with a lower risk of adverse effects. Herbal medicines such as Passiflora incarnata have been effective in supporting the gradual weaning of benzodiazepines, being indicated as a promising alternative, especially when supervised by a pharmacist. Given this, the introduction of herbal medicines as an alternative to benzodiazepines can reduce dependence and improve the quality of life of patients with anxiety disorders. The implementation of integrative practices and the role of the pharmacist are fundamental to ensuring a holistic and sustainable approach, promoting mental health in a safe way. This study reinforces the importance of public health policies in incorporating integrative and complementary practices into the Unified Health System (SUS), consolidating herbal medicines as part of care in the treatment of anxiety.Keywords: herbal medicines, benzodiazepines, anxiety, Integrative and Complementary Practices.